2007
DOI: 10.1108/07378830710755009
|View full text |Cite
|
Sign up to set email alerts
|

GIS and census data: tools for library planning

Abstract: Purpose -This article seeks to demonstrate a technique for using a Geographic Information System (GIS) to analyze US Census data to better understand potential library users and improve library service planning. Design/methodology/approach -A GIS was used to link variables such as age, race, income, and education from the 2000 US Census with service area maps of two proposed branch libraries. Thematic maps were created for each of the census variables to display demographic information about potential library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 12 publications
0
18
0
5
Order By: Relevance
“…Adkins and Sturges present a case study of the Phoenix, Arizona public library system where they demostrated the use of census information with GIS software for collection development, staffing, outreach, and service hours (Adkins &Sturges, 2004). Hertel and Sprague (2007) similary elaborated a study on East and West branch libraries in Boise, Idaho and demonstrated the usability of GIS to analyze US Census data to better understand potential library users and improve the library service plans on and for new library site selection.…”
Section: Related Workmentioning
confidence: 99%
“…Adkins and Sturges present a case study of the Phoenix, Arizona public library system where they demostrated the use of census information with GIS software for collection development, staffing, outreach, and service hours (Adkins &Sturges, 2004). Hertel and Sprague (2007) similary elaborated a study on East and West branch libraries in Boise, Idaho and demonstrated the usability of GIS to analyze US Census data to better understand potential library users and improve the library service plans on and for new library site selection.…”
Section: Related Workmentioning
confidence: 99%
“…Sin embargo, la mayor parte de los trabajos revisados en este artículo recogen aplicaciones para la visualización de datos bibliotecarios que ayudan a la toma de decisiones sobre la apertura, cierre o reubicación de bibliotecas (Preiser;Wang, 2006;Hertel;Sprague, 2007;Venuda, 2005). Mediante los códigos postales (o direcciones) de los usuarios, se puede utilizar un GIS para situar o eliminar nuevos centros bibliotecarios considerando la proximidad de estos servicios a los usuarios reales o potenciales, o incluso averiguando el nivel de solapamiento con la red de bibliotecas existente (Coyle, 2011).…”
Section: Usos De Gis En Bibliotecasunclassified
“…Muchas bibliotecas americanas emprendieron estudios sobre los usos y beneficios de dichos datos, llegando muchas a mejorar sus servicios de marketing mediante, por ejemplo, estudios demográficos de mercado o de demanda. Los GIS atrajeron inmediatamente la atención como herramientas especializadas en la creación de capas temáticas de datos demográficos visualizadas sobre mapas (Hertel;Sprague, 2007). Destaca el caso de The Public Library Geographic Database 5 (Koontz et al, 2004) que recoge datos de 17.000 bibliotecas públicas de Estados Unidos, en combinación con datos del censo.…”
Section: Usos De Gis En Bibliotecasunclassified
See 1 more Smart Citation
“…Theissen polygons, also known as vonoroi polygons are often used in accessibility studies (Brabyn & Skelly, 2002;Kwan & Weber, 2008). The suitability of Theissen polygons in identifying closest service providers to specific locations has resulted in it being applied in educational services such as determining accessibility to libraries (Park, 2012;Hertel & Sprague, 2007;Kinikin, 2004). Park (2012) carried out a study to assess physical accessibility of library.…”
Section: Theissen Polygonsmentioning
confidence: 99%